MIC and MBC of red fruit extract (Pandanus conoideus Lam) against periodontal pathogens bacteria - Martina Amalia; Vivi Oktavia Manik; Indrawati Jafar; Shaskhia Angelina Br Ginting (Faculty of Dentistry, Universitas Gadjah Mada, 2022)
There are only few studies on the antibacterial activity of red fruit extract (Pandanus conoideus Lam) against oral pathogenic bacteria. Thus, this study aims to determine the effectiveness of red fruit extracts by looking at the Minimum inhibitory Concentrations (MIC) and Minimal Bactericidal Concentrations (MBC) against periodontal pathogenic bacteria. The subjects of this study were Streptococcus mutans (ATCC 25175), Fusobacterium nucleatum (ATCC 25586), and Porphyromonas gingivalis (ATCC 33277). The antibacterial effectiveness of red fruit extract was tested by the liquid dilution method (microdilution). The data were analyzed using the one-way ANOVA test followed by a double comparison test with the Post Hoc Least Significance Different (LSD) test method. The red fruit extract effectively inhibited and eliminated test bacteria (p <0.05). Our study showed that the red fruit extracts at a concentration of 20% could inhibit the growth of Streptococcus mutans and Porphyromonas gingivalis, which was determined as the MIC strength of 80% as MBC of both bacteria tested. Furthermore, red fruit extract at the concentration of 10% showed an inhibitory effect on the growth of Fusobacterium nucleatum, which was determined as MIC of Fusobacterium nucleatum and the strength of 40% as MBC of Fusobacterium nucleatum. The red fruit extracts were significantly effective against the growth of Streptococcus mutans, Fusobacterium nucleatum, and Porphyromonas gingivalis provide essential information for further in vivo clinical studies to determine the exact dosage and clinical effectiveness of periodontal disease.